Biology Driven Targeted Therapy of Pediatric Soft-Tissue and Bone Tumors: Current Opportunities and Future Challenges (2016)
Recent advances in the understanding of the biological basis of pediatric soft-tissue and bone tumors, especially owing to the advent of “omics” technologies, have led to an exponential increase in the current knowledge on the genetic and cellular patho-mechanisms that drive these diseases. This offers the unprecedented opportunity to develop and implement targeted therapies such as monoclonal antibodies, small molecules, oncolytic viruses, and immunotherapies in standard and/or personalized treatment regimens. However, to date only a few examples document a successful translation of discoveries from the bench to the bedside. Recent international expert congresses such as the “Pediatric Cancer Translational Genomics” conference (Phoenix, Arizona, 2012), the ESF-EMBO workshop on “Molecular Biology and Innovative Therapies in Sarcomas” (Pultusk, Poland, 2012), and the AACR special meeting on “Pediatric Cancer at the Crossroads – Translating Discovery into Improved Outcomes” (San Diego, California, 2013) further emphasize the urgent need for a more rapid and especially more successful translational process. Hence, we strongly believe that a Frontiers Research Topic aiming at this aspect would fit just in time and that it would have great potential to receive numerous contributions of outstanding experts of the field. The proposed Frontiers Research Topic shall provide a platform for active and interdisciplinary discussion, summarize current state-of-the-art knowledge on all basic research and translational aspects in pediatric soft-tissue and bone tumors, and offer new perspectives of how to further promote and accelerate the translational process. We welcome high-quality original research articles, brief reports, as well as opinion, hypothesis, and review articles, and especially encourage submissions from early-career scientists.